Satu Dekade Pasca Invasi AS di Irak - Winarno, Budi (Jurnal Hubungan Internasional, 2014)
The main reasoning behind the United Statesâ attack on Iraq, March, 20th 2003 among others was a geopolitics factor in the context of keeping oil supply safely. Therefore, it has influenced how the United States implementing the process of democaratization in Iraq. Although a new government of Iraq has been established through a general election supervised by the US, security and peace are still far away. In the contrary, Iraq has been plunged into a civil war. The traditional Israeli-American relation has been a key factor to keep American vital interest in Middle East. However, the instability of Iraq, has been crucial in influencing the democratization and peace in Iraq, as well as peace and security in Middle East.